Determinan perilaku menabung dari Mahasiswa di NTT: Peran kontrol diri sebagai variabel intervening - Lejap, Hedwigh Hendrikus Temai; Wutun, Maria B. M. G.; Manafe, Henny A.; Bau Mau, Ignatia B. (MBR (Management and Business Review), 2023)
The main objectives of this study were to determine the level of financial literacy, family financial socialization, peers, self-control, and saving behavior based on socio-economic demographic factors of undergraduate students (S1) in NTT and to know the role of self-control as a mediator between the determinants and saving behavior. Using purposive sampling method, 321 respondent were taken from three universities. Data was collected using a questionnaire via google form, analyzed using SEM-PLS. The findings in the study show that most undergraduate students (S1) in NTT have high levels of financial literacy, family financial socialization, self-control, and saving behavior. Only peers are at a low level. In addition, self-control can be a mediator between financial literacy and socialization of family finances with the saving behavior of Undergraduate Students (S1) in NTT. Meanwhile, self-control cannot be a mediator between peers and saving behavior.